1993
DOI: 10.5144/0256-4947.1993.231
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Hepatitis B Vaccine into the Expanded Program on Immunization: The Saudi Arabian Experience

Abstract: Hepatitis B virus (HBV) is endemic in the Kingdom of Saudi Arabia. To prevent the chronic carriage of HBV in Saudi children, hepatitis B vaccine was added as the seventh immunogen in the expanded program on immunization (EPI). In the first year, the coverage of the first dose and third dose of HB vaccine was 90% and 73%, respectively. In a survey of 637 children, 603 (95%) were positive for antibody to hepatitis surface antigen (anti-HBs) without concomitant antibody to hepatitis B core antigen (anti-HBc) or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…This finding is in agreement with previous results reported by Mehdi et al [22], and this finding may be explained by the increased exposure encountered by males, non-governmental workers and those of an older age [21]. The significant high risk of HBV among married participants in this study could also be due to their older age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in agreement with previous results reported by Mehdi et al [22], and this finding may be explained by the increased exposure encountered by males, non-governmental workers and those of an older age [21]. The significant high risk of HBV among married participants in this study could also be due to their older age.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the prevalence of HBsAg in this study was low among students and this matched with that reported in the Najran study (1.7%) [10]. The Kingdom of Saudi Arabia introduced the national strategy of HBV vaccination of all children from 1990 [21]. Accordingly, nearly all students enrolled in this and other studies were born after that year, and it is expected that virtually all of them had received the HBV vaccination in the national programme.…”
Section: Discussionsupporting
confidence: 87%
“…Data gathered and also clinical experience indicate that HCV is perhaps more important than hepatitis B virus (HBV) in causing liver disease in the Saudi population. Furthermore, the integration of HBV vaccine into the Expanded Program on Immunization (EPI) 70 in Saudi Arabia in 1989 will undoubtedly greatly reduce the incidence of HBV infection in the future, leaving HCV as the major etiological agent of CLD among Saudis. 4) Studies from Saudi Arabia are in agreement with studies from different parts of the world, [71][72][73] regarding the lack of evidence for intrafamilial or sexual transmission of HCV.…”
Section: Genotypes Of Hcvmentioning
confidence: 99%
“…In Taiwan due immunization program of HBV, the percentage of HBV-related HCC in children and adolescents decreased [38,39] . In Saudi Arabia and Malaysia, the prevalence of HBV infection in children have declined since the beginning of the vaccination [40,41] . Iran is located in low risk area and characterized as low incidence rate of HCC (< 5 per 100000) [42] .…”
Section: Hepatitis B In Asiamentioning
confidence: 99%